A Feasibility study on Almaciga Resin Philippines, Inc. (ARPI) - Balagtas, Paula Marie L. (College of Engineering, 2003)
Almaciga is a very large tree reaching 300 cm in diameter at breast height and 60 meters in height. It is endemic in the Philippines and exists on mountain slopes throughout the archipelago. The Almaciga tree yields high quality resin. The resin is commonly known as Manila Copal in the international market and has been an article of commerce because of its wide array of uses. For many years, Almaciga-based resin is widely used in small to medium industries. It has specifically become an ingredient in the manufacture of various products such as high-grade varnishes and lacquers, textile paint, linoleum, plastic, pestecides, and others. It was an early export product of the Philippines, hence the identification Manila Copal. Locally, this is used as incense in religious ceremonies, for torches, starting fire, as caulking material for boats, and smudge for mosquitoes. It is also used in other processes as in making patent leather and sealing wax. Large quantities of this resin are also used in preparing sizing materials for pulp and paper manufacture. Almaciga resin can also be used as cation exchange resin for the removal of heavy metals from industrial wastewater. Resin combined with alkali rosin is used in soap making and in the production of rosin oils for special purposes. The high gloss varnish formulated using Almaciga resin has high total solids. This means less number of coatings to produce a surface quality comparable to commercially available varnish. One will need two coats of the Almaciga resin varnish instead of 3 to 4 coats with commercial varnish. The Almaciga resin varnish is resistant to liquids such as water, coffee, softdrinks and the like. This means spills on the finished items do not leave white spots or marks on the surface. Compared to varnish currently offered in the market, varnish made out of Almaciga resin is 100% cheaper. It is easily available. The ?premium? type of Almaciga resin varnish gives a natural high-gloss finish to products. Almaciga Resin Philippines, Incorporated (ARPI) aspires to reinforce the country?s supply of Almaciga resin or Manila Copal and to introduce the Almaciga resin varnish to small to medium-scale furniture and handicraft makers. Its vision which is to lead the way towards the development and growth of the natural resin industry, as well as, to become the leading Almaciga resin company in the Philippines. The company plans to achieve the enumerated visions by upholding the following missions: to recognize the need of the country for supply of the raw material Almaciga resins to numerous industries; to provide first-class Almaciga resin and Almaciga resin varnish at reasonable prices; to improve the welfare of indigenous people by granting job opportunities; and to support the government in their campaign against the exploitation of valuable resources such as Almaciga trees. The group dealt with the different aspects of a project feasibility study namely: (1) the market analysis; (2) the technical analysis; (3) financial analysis; and (4) the socio-profitability analysis. This was accomplished in behalf of the researchers and scientists of Forest Products and Research Development Institute (FPRDI) to serve as a reference in meeting the different areas concerning the particular matter. Care has been taken to make this paper as accurate as possible. The analytical tools and techniques presented using the available information and statistics can already serve the purpose of formulating strategies in setting up a company that purifies raw almaciga resin and produces Almaciga resin varnish.